Internalisasi Nilai-Nilai Pendidikan Multikultural di Pondok Pesantren Kiai Syarifuddin Wonorejo Lumajang - Mukhammad Ali Kafi; Ahmad Fauzi; Nasyrul Syarif (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Indonesia is a pluralistic nation because it consists of various tribes, religions, ethnicities, cultures and languages. This diversity is found in various regions spread from Sabang to Meraoke. Every Indonesian citizen is obliged to maintain this diversity by upholding the foundation of the Indonesian state and the motto of Bhinneka Tunggal Ika in order to create national unity. Looking at the existing phenomena and referring to previous research, there are still many undesirable events happening in the environment around us today. Therefore, it is necessary to internalize the values of multicultural education. From the description above, there are three focuses studied in this thesis, namely (1) how is the process of transforming the value of multicultural education in the Kiai Syarifuddin Wonorejo Lumajang boarding school? (2) how is the process of transacting the value of multicultural education in the Kiai Syarifuddin Wonorejo Lumajang boarding school? (3) how is the process of internalizing the value of multicultural education in the Kiai Syarifuddin Wonorejo Lumajang boarding school?. This research uses the type of field research, with a qualitative approach, The research subjects consisted of the head of the cottage, administrators, educators, and students, Data collection techniques were taken from interviews, observation, and documentation. Based on the results of the study, it can be seen that: (1) the value transformation process is educators use an approach to introduce students to good and bad values. (2) the value transaction process is educators conducting two-way communication or interaction between students and educators that are reciprocal. (3) The process of trans-internalization of this value is that the educator in front of the santri is no longer a physical figure, but his personality attitude or personality or mental communication that plays an active role. In this process, educators always provide examples of good values in everyday life.